Laparoscopic technique for left hemicolectomy and sigmoidectomy - Baca, Ivo (Endoskopska revija, 2009)
In the earliest report of laparoscopic colon resections in 1991, Jacobs, Florida, described his initial experience with Ćlaparoscopic-assistedĆ colon resection in 20 patients. In the past 15 years, thousands of colorectal resections have been performed all over the world. Skillful surgeons have consistently introduced new surgical techniques with excellent outcomes and thus motivated their colleagues to use these techniques in their patients. As a result laparoscopic resection has been adopted to treat conditions of all parts of the large intestine. This paper deals with left hemicolectomy and sigmoidectomy. These procedures can be regarded as technically most challenging surgical laparoscopic operations. Several techniques have been described for mobilizing and resecting the splenic flexure, descending colon, sigmoid, and rectum. We present our method with the aim to contribute to further development of laparoscopic colorectal surgery. Surgical strategies and techniques used in left hemicolectomy and sigmoidectomy are described and oncologically relevant aspects are considered. Between April 1996 and December2008, approx. 680 patients were treated by laparoscopic left hemicolectomy and sigmoidectomy using a standardised four-trocar laparoscopic surgical technique, described in this paper. The indications for surgery ranged from benign diseases to malignant conditions.
Keywords: Colonoscopy; Kolonoskopija; Methods; Predoperativna oskrba; Sigmoidoscopy; Sigmoidoskopija; Zdravljenje, izid; Patient Selection; Bolnik, izbor; Treatment Outcome; Preoperative Care; debelo črevo; laparoskopska kirurgija; kirurško zdravljenje